TEACHER SELF-DEVELOPMENT IN THE CONTEXT OF INCLUSIVE EDUCATION - PERCEPTIONS OF TEACHERS FROM A MUNICIPAL SCHOOL IN TAPAUÁ, AMAZONAS, BRAZIL - de Souza, Hosana Ferreira (Editora Impacto Científico, 2025)
Although inclusive education is a constitutional right of people with disabilities, its implementation in Brazilian schools is still fraught with flaws and gaps. Teacher self-training can be seen as an alternative to overcome the difficulties teachers face in terms of training for this educational modality. The study aims to elucidate teacher self-training in the context of inclusive education, through the perception of teachers from a municipal school located in Tapauá, Amazonas state. It is a bibliographic, exploratory, and mixed-methods study, which involved the participation of 9 elementary school teachers from a municipal school in Tapauá, a municipality in the state of Amazonas. A pedagogical booklet, part of a self-training program focused on inclusive education, was used. In Scenario 1, which preceded the dissemination of the booklet, it was noted that teachers demonstrated low knowledge about inclusion and its nuances. In Scenario 2, this panorama improved. Although acknowledging that much remains to be done, teachers have become aware of the need to make efforts to include students with disabilities in the school context. Given the perceived training difficulties in Tapauá, self-directed learning was seen as an interesting alternative for training in the inclusion of people with disabilities. However, the State, as the guarantor of education, must undertake efforts and create public training policies that result in the strengthening of teaching practices and, consequently, consolidate the enjoyment of citizenship and autonomy for students with disabilities. DOI: https://doi.org/10.56238/edimpacto2025.092-036